”Alltid saknad – aldrig glömd”: Om emotionella drivkrafter inom Missing People Sweden (Sociologisk Forskning, 2015)
”Forever missed – never forgotten”: Emotion and action in a swedish voluntary search and rescue organisationThe article explores the phenomenon of voluntary policing, through a case study of the voluntary search and rescue group Missing People Sweden (MPS). The article focuses on how a collectively upheld emotionology guide members’ views on the problem MPS is engaging, how this problem should be engaged, and why people should join MPS in its activities. The material used was gathered in spring 2014; through eight semi-structured interviews, document studies and four participant observations of the organisation’s activites. The results indicate that MPS members relate their views to an emotionology consisting of two separate themes; one of equality and collectivism, and one of individualism and meritocracy. The article demonstrates that the Tönniesian terms Gemeinschaft and Gesellschaft can both be applied to describe the organisation’s social environment. It also demonstrates that the Tönniesian dichotomy is a theoretical concept that is suited to the analysis of voluntary policing groups.